Traces of First and Second wave feminist thoughts in the writings of Adrienne Rich, Doris Lessing and Caryl Churchill - Zaman, Tanzina (BRAC University, 2016)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2015.